Integrasi Teori Belajar dalam Pengembangan Teknologi Pembelajaran Pendidikan Agama Islam di Era Digital - Sitti Rachmatia Saliha; Hadi Mahmud; Nurdin; Imelda Wahyuni (Kartika: Jurnal Studi Keislaman, 2026)
This article examines the integration of learning theories in the development of Islamic Religious Education (PAI) learning technology in the digital era. The study uses a qualitative library research method by analyzing classical and contemporary literature on behaviorism, cognitivism, constructivism, humanism, connectivism, instructional media, learning experience, and Islamic educational values. The findings show that behaviorism contributes to the formation of religious habits, cognitivism strengthens conceptual understanding, constructivism supports contextual and collaborative learning, and humanism develops self-awareness and spiritual reflection. These four theories are further strengthened by connectivism, which explains learning through digital networks; Dale's Cone of Experience, which clarifies the role of media in transforming abstract Islamic values into more concrete learning experiences; and Bruner's representational theory, which guides learning from enactive experience to iconic visualization and symbolic understanding. The article argues that PAI learning technology should not be reduced to technical media, but should be developed as an integrative pedagogical system rooted in Islamic values, critical digital literacy, and spiritual formation. This integrative model ensures that technology serves not merely as a delivery tool but as a transformative medium that connects habituation, conceptual understanding, social experience, spiritual reflection, knowledge networks, and representational learning